PTU-115 Efficacy of mycophenolate mofetil therapy in the management of inflammatory bowel disease. (28th May 2012) - Smith, M R; Wood, L; Slater, J; Cooper, S C
Abstract : Introduction: The role of Mycophenolate mofetil (MMF) as an immunomodulatory drug in managing inflammatory bowel disease is yet to be fully defined. We reviewed our experience of the efficacy, safety and tolerability of MMF in treating patients with refractory inflammatory bowel disease. Methods: A retrospective analysis was performed of the case records of all patients treated with MMF for inflammatory bowel disease at our institution between 2003 and 2011. Remission was assessed by reviewing clinical, endoscopic and laboratory indices. Results: We identified 36 patients, 23 male (64%) with a median age 46 yrs (range 19–75). Disease was classified as Crohn's disease in 19, ulcerative colitis 16, indeterminate colitis.1 33 patients (92%) had previously received azathioprine; 32 discontinued this due to side-effects. Five patients had undergone surgery for small bowel Crohn's disease. The starting dose of MMF was between 500 mg and 2 g daily, titrated to a dose of 2 g daily as tolerated. 26 patients (72%) were concurrently taking oral corticosteroids, and 18 (50%) were taking an oral 5-aminosalicylate. At 8 weeks, 29 patients (81%) had either achieved acute remission or maintained previous remission. Drug side-effects were experienced by eight patients (22%)—these symptoms were managed successfully by dose reduction in six patients (75%), with discontinuation in two patients. There were no serious haematological or other adverse drug effects. After 6 months of treatment, 33 patients continued to take MMF of which 19 patients (58%) had achieved sustained steroid-free remission. Median length of MMF treatment observed was 21.5 months (IQR 9.7–31.6). At the end of the observation period, 29 patients (81%) remained on MMF. 13 patients (36% of the original treatment group; UC 7, Crohn's 5) remained in steroid-free remission with median time of remission 21.4 months (IQR 11.0–30.0). A further 13 patients achieved sustained remission with the addition of corticosteroids and/or anti-TNF therapy. Five patients (14% overall) were refractory to all medical therapy and underwent surgery: colectomy for UC 3, right hemicolectomy for Crohn's. 2 Conclusion: From our experience, MMF may represent a promising alternative treatment for inducing and maintaining remission in patients intolerant of or unable to receive thiopurines. It appears well tolerated with a good safety profile in thiopurine intolerant subjects. Competing interests: None declared.